The meaning and essence of the business planning - Тохтамиш, Н. І.; Tokhtamysh, N. I.; Volobuieva, V. V.; Khazanovych, N. A. (Lulu Press, 2018)
The variability of macroeconomic factors requires from enterprises detailed forecasting of their strategic and current activities, considering the opportunities and threats of further development and realization of the set goals, the ability to make appropriate management decisions. An important element of strategic planning, in a decisive degree, can be the response of the enterprise to the requirements of the environment and maintain its appropriate behavior in the market, business planning. In the article, we give a definition of business planning, and we find out its role in the management of enterprises.
Keywords: business plan; strategic management; business system